Impact of Toll-Like Receptor-Specific Agonists on the Host Immune Response to the Yersinia pestis Plague rF1V Vaccine - Biryukov, Sergei; Dankmeyer, Jennifer L.; Shamsuddin, Zain; Velez, Ivan; Rill, Nathaniel O.; Rosario-Acevedo, Raysa; Klimko, Christopher P.; Shoe, Jennifer L.; Hunter, Melissa; Ward, Michael D.; Cazares, Lisa H.; Fetterer, David P.; et al. (Frontiers in Immunology, 2021)
Relatively recent advances in plague vaccinology have produced the recombinant fusion protein F1-V plague vaccine. This vaccine has been shown to readily protect mice from both bubonic and pneumonic plague. The protection afforded by this vaccine is solely based upon the immune response elicited by the F1 or V epitopes expressed on the F1-V fusion protein. Accordingly, questions remain surrounding its efficacy against infection with non-encapsulated (F1-negative) strains. In an attempt to further optimize the F1-V elicited immune response and address efficacy concerns, we examined the inclusion of multiple toll-like receptor agonists into vaccine regimens. We examined the resulting immune responses and also any protection afforded to mice that were exposed to aerosolized Yersinia pestis. Our data demonstrate that it is possible to further augment the F1-V vaccine strategy in order to optimize and augment vaccine efficacy.